Isolation of Flavonoids Compounds from Akalifa (Acalypha wilkesiana Muell. Arc.) Plant Leaves - Simangunsong, Siska NA; Lenny, Sovia; Marpaung, Lamek (Talenta Publisher, 2023)
Flavonoid compounds from the leaves of Akalifa (Acalypha wilkesiana Muell. Arc.) have been extracted with maceration by methanol solvent, then added with ethyl acetate and partition extracted with n-hexane. 6% HCl acidifies the concentrated methanol extract, then partition extracted with chloroform. The concentrated chloroform extract was separated by column chromatography with silica gel 40 as the stationary phase and n-hexane: ethyl acetate 90:10; 80:20; 70:30; 60:40; 50:50 (v/v) as the mobile phase. The compounds were purified with TLC preparative yielding tawny paste weighing 4 mg with Rf= 0.42 with eluent n-hexane: ethyl acetate 60:40 (v/v). The identified analysis by using Ultraviolet-Visible (UV-Vis) spectroscopy, Fourier Transform Infra Red Spectroscopy (FT-IR), and Proton Nuclear Magnetic Resonance (1H-NMR) Spectroscopy was estimated as a flavonoid is an isoflavone.